Gene-culture coevolution: toward a general theory of vertical transmission. - Feldman, M W (1992)
A general formulation of cultural and genetic transmission is developed. The cultural transmission is vertical and the genetics may involve multiple loci. Each individual is represented by a phenogenotype, and conditions are given under which the evolutionary dynamics of phenogenotype frequencies are reducible to phenogametic or phenoallelic frequencies. The interaction between genes and culture is specified by an association measure, and results on the order of magnitude of this association at equilibrium are presented.